THE ROLE OF MUSIC IN CENTRAL ASIAN SUFI TRADITIONS - Ergashov Abbos Baxridinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the role and significance of music within the Sufi traditions of Central Asia. It explores how musical practices have functioned as spiritual, educational, and cultural instruments in the region’s Sufi heritage. The study highlights the integration of music into ritual practices, poetic expression, and moral education, emphasizing its contribution to spiritual refinement and communal cohesion. By analyzing historical sources and Sufi practices in Central Asia, the research underscores the enduring importance of music as a means of spiritual experience and cultural continuity.